Effects of 6 Months of Active Commuting and Leisure-Time Exercise on Fibrin Turnover in Sedentary Individuals with Overweight and Obesity: A Randomised Controlled Trial - Anne Sofie Gram; Martin Bæk Petersen; Jonas Salling Quist; Mads Rosenkilde; Bente Stallknecht; Else-Marie Bladbjerg (Journal of Obesity)
Obesity and exercise constitute important factors for cardiovascular disease risk, but the long-term effects of different exercise modalities on haemostatic biomarkers are not well elucidated. We investigated the effects of 6 months of active commuting or leisure-time exercise on measures of fibrin turnover in individuals who are overweight and obese. Ninety younger (20–40 years), sedentary, healthy women and men who are overweight and obese (BMI: 25–35 kg/m2) were randomised to 6 months of habitual lifestyle (CON, n=16), active commuting (BIKE, n=19), or leisure-time exercise of moderate (MOD, ∼50% VO2peak reserve, n=31) or vigorous intensity (VIG, ∼70% VO2peak reserve, n=24). Fasting blood samples (baseline and 3 and 6 months) were analysed for cholesterols and triglycerides, thrombin generation, prothrombin fragment 1 + 2, D-dimer, fibrin clot properties, and fibrinolytic activity. We observed no differences between CON, BIKE, MOD, and VIG during the intervention and no time effects for any of the variables measured despite increased VO2peak in all exercise groups. We found no difference between CON and all exercise groups combined and no gender-specific effects of exercise. Our findings suggest that thrombin generation capacity, coagulation activation, fibrin clot structure, and lysability are unaffected by long-term active commuting and leisure-time exercise in women and men who are overweight and obese.